당뇨병성 족부 궤양 환자의 진단 1년 내의 절단율 및 위험 인자의 분석 - 천동일; 전민철; 최성우; 김용범; 노재휘; 원성훈; Chun, Dong-Il; Jeon, Min Chul; Choi, Sung-Woo; Kim, Yong-Beom; Nho, Jae-Hwi; Won, Sung Hun (대한족부족관절학회지, 2016)
Purpose: This study investigates the amputation rate within 1 year after the diagnosis of diabetic foot ulcer and its associated risk factors. Materials and Methods: This study enrolled 60 patients with diabetic foot ulcer. The mean and standard deviation age was $64.4{±}12.8years$ (range, 32~89 years); the mean and standard deviation prevalence period for diabetes mellitus was $21.0{±}7.5years$ (range, 0.5~36 years). The amputation rate was evaluated by dividing the subjects into two groups - the major and minor amputation groups - within 1 year following the initial diagnosis of diabetic foot ulcer. Multivariate Cox proportional hazards regression analysis was used to identify the risk factors for amputation. Results: The total amputation rate of 38.3% (n=23) was comprised of the amputation rate for the major amputation group (10.0%) and rate for the minor amputation group (23.8%). There was a high correlation between peripheral artery disease (toe brachial pressure index <0.7) and amputation (hazard ratio [HR] 5.81, confidence interval [CI] 2.09~16.1, p<0.01). Nephropathy was significantly correlated with the amputation rate (HR 3.53, CI 1.29~9.64, p=0.01). Conclusion: Clinicians who treat patients with diabetic foot complications must understand the fact that the amputation rate within 1 year is significant, and that the amputation rate of patients with peripheral artery disease or nephropathy is especially high.